Standardisasi Simplisia dan Ekstrak Daun Jambu Mete (Anacardium occidentale L.) dari Kabupaten Gowa Sulawesi Selatan - Asyari Al Hutama Azis; Yani Pratiwi; Irva Maulidiyah Putri (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
Cashew leaves (Anacardium occidentale L.) contain secondary metabolite compounds such as flavonoids, tannins, polyphenols, alkaloids, saponins, and phenolics, which exhibit pharmacological activities, including antioxidant and antibacterial properties. Traditionally, cashew leaves are used by the people of Gowa Regency to treat diabetes mellitus, oral inflammation, burns, muscle aches, and skin infections such as acne and boils. This study aims to evaluate the quality of cashew leaf raw materials from Gowa Regency based on specific parameters, namely water-soluble and ethanol-soluble extract content in the simplicia. Additionally, nonspecific parameters were evaluated, including drying loss, total ash content, and acid-insoluble ash content in the simplicia, as well as water content, total ash content, and acid-insoluble ash content in the extract, according to the Indonesian Herbal Pharmacopoeia Edition II (2017). Extraction was performed using the maceration method with 70% ethanol, yielding 21.2%. The results showed that the simplicia contained 13.46% water-soluble extract, 18.23% ethanol-soluble extract, 9.93% drying loss, 3.03% total ash, and 0.71% acid-insoluble ash. Meanwhile, the extract showed a water content of 18.26%, total ash of 0.89%, and acid-insoluble ash of 0.39%. Both the simplicia and extract of cashew leaves from Gowa Regency met the quality requirements of the Indonesian Herbal Pharmacopoeia Edition II (2017) and were categorized as high quality.